2016
DOI: 10.1002/anie.201509653
|View full text |Cite
|
Sign up to set email alerts
|

Combining Metabolic Engineering and Electrocatalysis: Application to the Production of Polyamides from Sugar

Abstract: Biorefineries aim to convert biomass into a spectrum of products ranging from biofuels to specialty chemicals. To achieve economically sustainable conversion, it is crucial to streamline the catalytic and downstream processing steps. In this work, a route that combines bio- and electrocatalysis to convert glucose into bio-based unsaturated nylon-6,6 is reported. An engineered strain of Saccharomyces cerevisiae was used as the initial biocatalyst for the conversion of glucose into muconic acid, with the highest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
127
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 122 publications
(136 citation statements)
references
References 43 publications
6
127
0
3
Order By: Relevance
“…Due to its acid tolerance and resistance to microbial contaminations, Saccharomyces cerevisiae makes an ideal host organism for production of cis,cis-muconic acid, and thus the pathway has been successfully implemented in S. cerevisiae by several groups (5)(6)(7)(8). Several approaches have been applied to improve the yield of the pathway.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Due to its acid tolerance and resistance to microbial contaminations, Saccharomyces cerevisiae makes an ideal host organism for production of cis,cis-muconic acid, and thus the pathway has been successfully implemented in S. cerevisiae by several groups (5)(6)(7)(8). Several approaches have been applied to improve the yield of the pathway.…”
mentioning
confidence: 99%
“…Several approaches have been applied to improve the yield of the pathway. These approaches include deletion or inactivation of the E-domain of the pentafunctional yeast enzyme Aro1 responsible for the shikimate 5-dehydrogenase function of the enzyme (5,7), leading to accumulation of the precursor 3-DHS. Overexpression of a feedback-resistant mutant of 3-deoxy-D-arabino-heptulosonate-7-phosphate synthase ARO4 improved entry of precursors into the shikimic acid pathway (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…One approach, which we have recently reported, entails the use of electrochemistry to mitigate the extensive separations that would be required for the conversion of biologically produced intermediates such as muconic acid (MA). 17,18 MA is a C 6 unsaturated dicarboxylic acid produced by the fermentation of cellulosic sugars and lignin-derived aromatics. In addition to recent efforts led by industry, in particular by Deinove 19 and Myriant, 20 several academic research groups have reported producing MA with high yields and titers using metabolically engineered bacteria: e.g., Escherichia coli reached 59.2 g MA L -1 at a 30% (mol MA /mol Glucose ) yield, 21 and Pseudomonas putida achieved >15 g MA L -1 using the aromatic lignin monomer p-coumarate as a feedstock.…”
Section: Introductionmentioning
confidence: 99%
“…17 These efforts have been motivated by MA's potential as a platform molecule to produce a vast array of renewable monomers of industrial importance, including adipic acid, terephthalic acid, caprolactone, 1,6-hexanediol, and 1,6-hexamethylenediamine. 18 Building blocks derived from MA are central to the manufacture of Nylon-6,6, polyethylene terephthalate (PET), and other polyesters, polyamides, and polyurethanes with an estimated global annual market greater than 22 billion U.S. dollars.…”
Section: Introductionmentioning
confidence: 99%